THE EXISTENCE OF THE CRIMINAL THREAT OF THE DEATH PENALTY IN THE CRIMINAL ACT OF CORRUPTION IN INDONESIA - Utreck Ricardo; Firman Halawa (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The uncontrolled increase in criminal acts of corruption will bring disaster not only to national economic life but also to the life of the nation and state in general. The Corruption Eradication Commission took over the investigation and prosecution as intended on the grounds that public reports regarding criminal acts of corruption were not followed up, the process of handling criminal acts of corruption was protracted or delayed without justifiable reasons. The purpose of this research is to find out and analyze what is the legal basis for the Corruption Eradication Commission's authority to carry out investigations and prosecutions? What are the obstacles faced by the Corruption Eradication Commission in carrying out investigations and prosecutions of corruption crimes? The research method used is normative juridical. The type of data used is secondary data. The results of the research are that the authority of the Corruption Eradication Commission to handle corruption cases is regulated in Article 6 letter c of the Corruption Eradication Commission Law which states that the Corruption Eradication Commission has the task of carrying out inquiries, investigations and prosecution of criminal acts of corruption. However, the Corruption Eradication Commission has additional authority, namely that it can take over corruption cases even if they are being handled by the Police or Prosecutor's Office (Article 8 paragraph (2) of the Corruption Eradication Committee Law). However, the takeover of the corruption case must be for the reasons stipulated in Article 9 of the Corruption Eradication Committee Law. Apart from the authority to take over corruption cases, there are other things that fall under the authority of the Corruption Eradication Committee, namely as regulated in Article 11 of the Corruption Eradication Commission Law and Article 50 of the Corruption Eradication Commission Law. The conclusion is that mutually agreed arrangements are needed to eliminate the notion that there is overlapping authority in terms of who has the authority to prosecute criminal acts of corruption that emerged after the issuance of the Law.